Reconceptualising brand identity in a dynamic environment - Silveira, C. (2015)
Brand identity definitions predominately take a unilateral and aspirational perspective—what managers want the brand to be—while emphasizing the need for stability over time. The increasingly dynamic environment and the rising role of consumers as co-contributors to brand construction and development demand rethinking this perspective. This paper seeks to advance the established conceptualization of brand identity by revising the definition and proposing brand identity as dynamic, constructed over time through mutually influencing inputs from managers and other social constituents (e.g., consumers). Drawing on a seminal definition from the field of sociology, underpinning the socially constructed nature of identity, the authors propose an innovative managerial framework that challenges established approaches of brand identity, within the new market context.